Rearing Success Does Not Improve With Apparent Pair Coordination in Offspring Provisioning - Ihle, Malika; Pick, Joel L.; Winney, Isabel S.; Nakagawa, Shinichi; Schroeder, Julia; Burke, Terry (Frontiers in Ecology and Evolution, 2019)
In species with biparental care, behavioural coordination in the provisioning of the progeny is hypothesized to increase the number of offspring that survive to independence. Coordination is often quantified by two metrics, alternation and synchrony. Turn-taking (leading to an alternation pattern) can result when one parent’s investment strategy is based on the investment of its partner (i.e. conditional cooperation). This should increase the overall provisioning rate and improve offspring body condition. Synchrony might equalise food delivery among offspring and therefore decrease the variance in offspring body condition within the brood. Overall, offspring survival could be increased by parental coordination. Finally, pairs with low coordination, and with potentially lower reproductive success, are expected to be more likely to divorce. In this study, we use a dataset on 473 pairs of house sparrows in a natural insular population to test these hypotheses. We found no effect of the pair’s apparent coordination on offspring condition, offspring survival, or divorce rate, questioning the adaptive significance of this behaviour. We argue that, in this species, the detection of a higher frequency of alternation and synchrony, when compared to chance expectation, might be induced by the environment, rather than result from an emergent pair behaviour selected for fitness benefits.